Current Sensorless Control Strategy for Nine-Level Packed-E-Cell Rectifier - Guler, Naki; Komurcugil, Hasan; Bayhan, Sertac; Biricik, Samet (IEEE, 2021)
In this study, a current control strategy is proposed for nine-level packed-E-cell (PEC) rectifier without using current sensor. The proposed control strategy is based on mathematical model of rectifier. A modulation signal is obtained from the differential equation of the system. The modulation signal requires the inductor current reference whose amplitude is obtained by using a proportional-integral (PI) regulator. The input signal to the PI regulator is the dc load voltage error. Hence, while the grid current control is achieved by the proposed control, the regulation of load voltage is achieved by PI. The performance of the proposed control strategy is tested under load variations, reference load voltage change, and grid voltage variation. Moreover, the robustness of the proposed control method under inductance variations is also investigated. Computer simulations are conducted to show the steady-state and dynamic performances of the proposed control method.
47th Annual Conference of the IEEE-Industrial-Electronics-Society (IECON) -- OCT 13-16, 2021 -- ELECTR NETWORK
Keywords: Packed-E-cell (PEC) rectifier; proportional-integral control (PI); current control